A preparation process of a high temperature humidity sensor resistant to water vapor aging

By using a specific proportion of amorphous toner and Y2O3 mixed cavity slurry in a high temperature and humidity sensor, the Y2O3 content at the cathode interface is increased, and the problem of poor water vapor aging resistance of the sensor is solved, achieving a longer service life and better service Accurate detection signal.

CN117024138BActive Publication Date: 2025-02-25JIANGSU UNIQUE ADVANCED MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311005408.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-25
Estimated Expiration
2043-08-10

AI Technical Summary

Technical Problem

The existing zirconia extreme current type high temperature and humidity sensors have poor water vapor aging resistance, resulting in a shortened service life and poor detection signal accuracy.

Method used

The cavity slurry is used to mix amorphous toner and Y2O3 according to mass ratio (94.5-99.5): (0.5-5.5), and the Y2O3 content at the cathode Pt/YSZ interface is increased to form a stable cubic ZrO2 to prevent the aging of water vapor. Go deeper into the interior.

Benefits of technology

It improves the water vapor aging resistance of the high-temperature humidity sensor, extends the service life, and improves the accuracy of the detection signal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117024138B_ABST
    Figure CN117024138B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of sensors, and specifically relates to a preparation process of a high-temperature humidity sensor resistant to water vapor aging, comprising the following steps: rolling milling: mixing YSZ powder, dispersant, solvent, binder, and plasticizer, adding zirconium ball milling medium to roll milling to uniformly slurry, and obtaining slurry; casting the slurry to make a green porcelain belt; punching holes on the green porcelain belt; printing: printing electrode slurry and cavity slurry on the green porcelain belt with a screen; lamination; cutting; sintering; the cavity slurry is made of amorphous carbon powder and Y2O3 mixed in a mass ratio of (94.5-99.5): (0.5-5.5). The present application increases the Y2O3 content at the cathode Pt / YSZ interface by adding cavity slurry in the hole, thereby improving the water vapor aging resistance of the high-temperature humidity sensor, thereby improving the detection signal accuracy and service life of the high-temperature humidity sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sensors, and in particular relates to a preparation process of a high-temperature humidity sensor resistant to water vapor aging. Background Art

[0002] Humidity and temperature parameter control is of great significance in the fields of textile, papermaking, food, boiler, wood drying, etc. Internationally, the humidity of high-temperature air medium is usually measured by the percentage of water vapor. For high-temperature (≥100°C) environments, commonly used humidity sensors, such as polymer humidity sensors and electrolyte humidity sensors, often perform worse in high-temperature environments than in low-temperature environments.

[0003] The zirconia limiting current oxygen sensor is based on the linear relationship between the oxygen partial pressure in high-temperature air and its humidity. It can indicate the humidity of the high-temperature environment by measuring the oxygen concentration in the high-temperature environment.

[0004] However, the applicant believes that the existing zirconia limiting current type oxygen sensor has poor resistance to water vapor aging, which leads to a shortened service life of the zirconia limiting current type high temperature humidity sensor and poor accuracy of the sensor detection signal. Summary of the invention

[0005] In order to improve the defect of the existing zirconium oxide limiting current type oxygen sensor that is poorly resistant to water vapor aging, the present application provides a preparation process for a high-temperature humidity sensor that is resistant to water vapor aging.

[0006] In a first aspect, the present application provides a preparation process of a high-temperature humidity sensor resistant to water vapor aging, which is implemented by the following technical solution:

[0007] A preparation process of a high temperature humidity sensor resistant to water vapor aging comprises the following steps:

[0008] Rolling slurry: Mix YSZ powder, dispersant, solvent, binder and plasticizer, add zirconium ball mill and roll evenly to obtain slurry;

[0009] Casting the slurry into a green porcelain tape;

[0010] punching holes in the green porcelain tape;

[0011] Printing: printing electrode slurry and cavity-making slurry on the green porcelain tape using a screen;

[0012] Lamination;

[0013] Cutting;

[0014] sintering;

[0015] The cavity forming slurry is prepared by mixing amorphous carbon powder and Y2O3 in a mass ratio of (94.5-99.5): (0.5-5.5).

[0016] By adopting the above technical scheme, the cavity-making slurry is mixed with amorphous carbon powder and Y2O3 in a mass ratio of (94.5-99.5): (0.5-5.5). The amorphous carbon powder in the cavity-making slurry will be burned out during the sintering process, and the Y2O3 in the cavity-making slurry will be deposited at the cathode Pt / YSZ interface. The additional Y2O3 content is increased on the basis of the original green porcelain belt, that is, the Y2O3 content at the cathode Pt / YSZ interface can be increased, the surface solid solution oxygen vacancy content is increased, and stable cubic ZrO2 is formed on the surface, which prevents water vapor aging from penetrating into the interior, stabilizes the length of the Pt / air / YSZ three-phase interface, and improves the water vapor aging resistance of the high-temperature humidity sensor. However, the applicant found in the research process that if the Y2O3 content in the cavity-making slurry is too high, Y2O3 will be doped into the zirconia crystal during the sintering process. The excessive addition of Y2O3 content at the cathode Pt / YSZ interface will affect the effective space of the diffusion cavity and the size of the Pt / air / YSZ three-phase interface, reduce the activity of Pt, and affect the detection performance of the high-temperature humidity sensor. If the Y2O3 content in the cavity-making slurry is low, it cannot increase the Y2O3 content at the cathode Pt / YSZ interface well, and the effect of improving the water vapor aging resistance of the high-temperature humidity sensor is not obvious.

[0017] Preferably, the cavity forming slurry is formed by mixing amorphous carbon powder and Y2O3 in a mass ratio of 97:3.

[0018] By adopting the above technical solution, the high temperature humidity sensor has good resistance to water vapor aging, and the detection signal of the high temperature humidity sensor has high accuracy and long service life.

[0019] Preferably, the particle size D of Y2O3 in the cavity forming slurry is 50 It is 50-100nm.

[0020] By adopting the above technical scheme, Y2O3 can be stably deposited at the cathode Pt / YSZ interface. During the sintering process, Y2O3 will be doped into the zirconia crystal, increasing the surface solid solution oxygen vacancy content, forming stable cubic ZrO2 on the surface, preventing water vapor aging from penetrating into the interior, and stabilizing the length of the Pt / air / YSZ three-phase interface, thereby improving the water vapor aging resistance of the high temperature humidity sensor.

[0021] Preferably, the particle size of Y2O3 in the cavity forming slurry is 80nm.

[0022] By adopting the above technical solution, Y2O3 can be deposited more stably at the cathode Pt / YSZ interface, and the high-temperature humidity sensor has better resistance to water vapor aging.

[0023] Preferably, the particle size D of the YSZ powder is 50 0.2-0.5μm.

[0024] YSZ powder is Y2O3 doped stable zirconium oxide. The particle size of YSZ powder is D 50 The particle size is 0.2-0.5 μm, and the small particle size can reduce the breaking of Zr-O-Zr(Y) bonds and the formation of Zr-OH due to the phase stability of polycrystalline materials, thereby reducing the precipitation of Y(OH)3, which is beneficial to improving the water vapor aging resistance of high temperature humidity sensors. However, the applicant found in the research process that the particle size D of Y2O3 doped stable zirconia 50 The particle size of Y2O3-doped zirconia is less than 0.2 μm, and it is difficult to disperse the Y2O3-doped zirconia in slurry and cast it into a green porcelain tape. 50 When the particle size is greater than 0.5 μm, the effect of reducing the precipitation of Y(OH)3 is not obvious, which is not conducive to improving the water vapor aging resistance of the high temperature humidity sensor.

[0025] Preferably, the particle size D of the YSZ powder is 50 It is 0.3μm.

[0026] By adopting the above technical scheme, the Y2O3-doped stable zirconia slurry has good dispersibility, and can effectively reduce the breaking of Zr-O-Zr(Y) bonds and the formation of Zr-OH, and has a good effect in reducing the precipitation of Y(OH)3, which is beneficial to further improve the water vapor aging resistance of the high temperature humidity sensor.

[0027] Preferably, the YSZ powder is 4-6 mol% yttria-stabilized zirconia powder.

[0028] During the research process, the applicant found that too low Y2O3 doping will affect the rate of ion migration in the solid electrolyte layer, and too high Y2O3 doping will cause the strength of zirconia to be greatly reduced, affecting its processing and use.

[0029] Preferably, the YSZ powder is 5 mol % yttria-stabilized zirconia powder.

[0030] By adopting the above technical solution, when the Y2O3 doping amount in the Y2O3-doped stable zirconia is 5 mol%, the electrical conductivity is high, the rate of ion migration is high, the strength of the zirconia will not decrease, and it is easy to process and use.

[0031] Preferably, the mass ratio of the YSZ powder, dispersant, solvent, binder and plasticizer is 1: (0.01-0.03): (0.5-0.6): (0.17-0.20): (0.06-0.08).

[0032] More preferably, the mass ratio of the YSZ powder, dispersant, solvent, binder and plasticizer is 1:0.02:0.55:0.18:0.07.

[0033] In the present application, the dispersant is selected from one or more of tributyl phosphate, triethanolamine, castor oil, oleic acid, triolein, polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol; preferably, the dispersant is triolein.

[0034] In the present application, the solvent is selected from one or more of anhydrous ethanol, n-propanol, n-butanol, toluene, xylene, dimethylacetamide and tributyl citrate.

[0035] Preferably, the solvent is a mixture of anhydrous ethanol, n-propanol and xylene.

[0036] Preferably, the volume ratio of anhydrous ethanol, n-propanol and xylene is 1:(0.5-0.7):(0.3-0.5).

[0037] More preferably, the volume ratio of anhydrous ethanol, n-propanol and xylene is 1:0.6:0.4.

[0038] In the present application, the binder is polyvinyl butyral.

[0039] In the present application, the plasticizer is selected from one or more of dibutyl phthalate, dioctyl phthalate, polyethylene glycol and triethylene glycol diisooctanoate; preferably, the plasticizer is dioctyl phthalate.

[0040] In the present application, holes are punched on the green porcelain tape according to the functional hole requirements to form an annular diffusion cavity hole with an inner diameter of 1.7 mm and an outer diameter of 3.3 mm.

[0041] In the present application, cavity-forming slurry is added into the diffusion cavity holes, and the amount of the cavity-forming slurry added is 25-30 mg / hole; preferably, the amount of the cavity-forming slurry added is 28 mg / hole.

[0042] In the present application, the electrode slurry is Pt slurry.

[0043] Preferably, the sintering includes sintering to form a sintered body, chamfering the sintered body and re-firing.

[0044] By adopting the above technical solution, sintering can refine the grains of zirconium oxide and improve the water vapor aging resistance of the high temperature humidity sensor. Re-firing after chamfering can recrystallize the surface of the sintered body to form a more stable cubic phase crystal layer, thereby improving the low temperature aging resistance of the high temperature humidity sensor.

[0045] Preferably, the re-firing temperature is 900-1200° C. and the re-firing time is 1-2 hours.

[0046] By adopting the above technical solution, the recrystallization effect of the sintered body surface is good, and the high temperature humidity sensor has good low temperature aging resistance.

[0047] In summary, this application has the following beneficial effects:

[0048] 1. The high temperature humidity sensor prepared in this application has good resistance to water vapor aging, long service life and good sensor detection signal accuracy.

[0049] 2. This application uses a cavity-making slurry mixed with amorphous carbon powder and Y2O3 in a mass ratio of (94.5-99.5): (0.5-5.5) to increase the Y2O3 content at the cathode Pt / YSZ interface and improve the water vapor aging resistance of the high-temperature humidity sensor.

[0050] 3. This application adopts the method of reducing the particle size D of Y2O3-doped stable zirconium oxide 50 , which reduces the precipitation of Y(OH)3 and is beneficial to improving the water vapor aging resistance of the high temperature humidity sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a process flow chart for preparing a high-temperature humidity sensor resistant to water vapor aging according to the present application.

[0052] Figure 2 The high temperature humidity sensor detection signal change effect prepared in Example 1-3.

[0053] Figure 3 The detection signal change effect of the high temperature humidity sensor prepared in Example 1 and Comparative Examples 1-2.

[0054] Figure 4 The detection signal change effect of Example 1 and the existing zirconium oxide limiting current type oxygen sensor 1-2 on the market. DETAILED DESCRIPTION

[0055] In this application, the water vapor aging process of the zirconia limiting current type oxygen sensor gradually and steadily extends from the surface to the inside of the YSZ matrix through nucleation and growth, and is characterized by surface roughness, grain precipitation and microcracks, and overall reduced mechanical properties. During the research process, the applicant found that the reasons why the zirconia limiting current type high temperature humidity sensor has poor water vapor aging resistance are:

[0056] 1. Main material: Yttrium-stabilized zirconia YSZ will rapidly decay its mechanical properties under a specific temperature (100-500°C) and water vapor environment, and water vapor aging will occur. The mechanism of this is: the surface of YSZ will chemically adsorb H2O molecules, and the H2O molecules will dissociate to produce H + and OH - , OH - Has a lower charge, OH - With O2 - The size is similar, high temperature will intensify the dissociation behavior of H2O molecules and promote OH - Diffusion into the YSZ lattice, and occupy the original Y2O3 formed oxygen vacancies, with the similar Y 3+ 、Zr 4+ Y-OH and Zr-OH bonds are formed, stress concentration points are generated, and Y atoms precipitate to form Y(OH)3, which changes the stable state of Y2O3-stabilized zirconia on the surface.

[0057] 2. Sensor structure characteristics: The electrode / electrolyte interface of the zirconia limiting current oxygen sensor is mostly Pt / YSZ electrode structure, and H2O molecules dissociate to produce H + and OH - , there is 2H near the cathode of the Pt electrode + +2e - =H2 reaction will promote OH - The generation of OH - The diffusion of oxygen at the electrode interface causes the precipitation of Y atoms of yttrium-stabilized zirconia YSZ in the Pt / YSZ interface to generate Y(OH)3, which in turn generates microcracks, leading to changes in the length of the Pt / air / YSZ three-phase interface, and further affecting the adsorption and diffusion of oxygen at the electrode interface and the O(Pt electrode) / O2 - The transmission of (in YSZ) also has an impact, which ultimately leads to large changes in the sensor test signal.

[0058] Therefore, improving the water vapor aging resistance of zirconia limiting current oxygen sensors is the key to preparing high-quality high-temperature humidity sensors.

[0059] The present application is further described in detail below with reference to the embodiments. Example

[0060] Embodiment 1 provides a preparation process of a high-temperature humidity sensor resistant to water vapor aging, the steps of which are as follows:

[0061] S1, 100kg D 50YSZ powder with a particle size of 0.3 μm and Y2O3 doping of 5 mol%, 2 kg of triolein, 55 kg of solvent, 18 kg of polyvinyl butyral and 7 kg of dioctyl phthalate were mixed, and zirconium ball milling medium was added to roll and grind into a uniform slurry to obtain a slurry;

[0062] S2, the slurry prepared in S1 is cast by a tape casting machine, the scraper height is controlled at 150μm, and the tape passes through a drying tunnel at a belt speed of 0.5m / min. The total length of the drying tunnel is 10m, and the temperatures of the three temperature zones are 30℃, 45℃, and 60℃ respectively. The green porcelain tape with certain flexibility and processability can be obtained by peeling it off from the dried carrier film;

[0063] S3, punching holes in the green porcelain tape prepared in S2 to form an annular diffusion cavity hole with an inner diameter of 1.7 mm and an outer diameter of 3.3 mm;

[0064] S4, 970g amorphous carbon powder and 30g particle size D 50 The cavity-forming slurry is mixed with 80nm Y2O3, and the cavity-forming slurry is printed in the diffusion cavity hole with a screen, and the amount of cavity-forming slurry added is 28mg / hole; Pt slurry is printed on the green porcelain tape with a screen;

[0065] S5, stacking the layers of raw porcelain together in sequence according to the functional requirements, and then pressing them together by isostatic pressing;

[0066] S6, cutting; cutting the laminated green porcelain blocks with a cutting knife;

[0067] S7, sintering: in a high temperature furnace without pressure at 2 o C / min heating up to 400 o C, 400 o C for 2 h, then at 5 o C / min heating up to 1400 o C for 2h and high temperature sintering, from 1400 o C with 10 o The cooling rate was reduced to 1200 °C / min. o C, naturally cool to form a sintered body, grind the edges and corners of the sintered body, and re-sinter the chamfered sintered body at 900°C for 2h to obtain a high-temperature humidity sensor resistant to water vapor aging, which is recorded as sensor-A;

[0068] The solvent is a mixture of anhydrous ethanol, n-propanol and xylene, and the volume ratio of anhydrous ethanol, n-propanol and xylene is 1:0.6:0.4;

[0069] The model of polyvinyl butyral is kpl-65874, which was purchased from Shandong Kepler Biotechnology Co., Ltd.

[0070] Example 2 provides a preparation process of a high temperature humidity sensor resistant to water vapor aging, which is different from Example 1 only in that the cavity forming slurry is composed of 995g amorphous carbon powder and 5g particle size D 50 It is mixed with 80nm Y2O3.

[0071] The high temperature humidity sensor resistant to water vapor aging prepared in Example 2 is denoted as Sensor-B.

[0072] Example 3 provides a preparation process of a high temperature humidity sensor resistant to water vapor aging, which is different from Example 1 only in that the cavity forming slurry is composed of 945g amorphous carbon powder and 55g particle size D 50 It is mixed with 80nm Y2O3.

[0073] The high-temperature humidity sensor resistant to water vapor aging prepared in Example 3 is denoted as Sensor-C.

[0074] The high temperature humidity sensors resistant to water vapor aging prepared in Example 1 and Example 2-3 were placed in an environment with a temperature of 200°C and a humidity of 95% for testing. The effect of the detection signal change of the high temperature humidity sensors prepared in Example 1-3 is shown in detail. Figure 2 .

[0075] Depend on Figure 2 It can be seen that the cavity forming slurry in Example 1 is mixed with amorphous carbon powder and Y2O3 in a mass ratio of 97:3, and the corresponding high temperature humidity sensor has better water vapor aging resistance. This is because the Y2O3 content in Example 2 (the mass ratio of amorphous carbon powder and Y2O3 is 99.5:0.5) is low, and the Y2O3 content at the cathode Pt / YSZ interface cannot be well increased, resulting in the water vapor aging resistance of the high temperature humidity sensor corresponding to Example 2 being not as good as that of the high temperature humidity sensor corresponding to Example 1; while the Y2O3 content in Example 3 (the mass ratio of amorphous carbon powder and Y2O3 is 94.5:5.5) is high, and Y2O3 will be doped into the zirconia crystal during the sintering process. The excessive increase of Y2O3 content at the cathode Pt / YSZ interface will affect the effective space of the diffusion cavity and the size of the Pt / air / YSZ three-phase interface, reduce the Pt activity, and affect the detection performance of the high temperature humidity sensor, resulting in the water vapor aging resistance of the high temperature humidity sensor corresponding to Example 3 being not as good as that of the high temperature humidity sensor corresponding to Example 1.

[0076] Comparative Example

[0077] Comparative Example 1 provides a preparation process of a high-temperature humidity sensor resistant to water vapor aging, which is different from Example 1 only in that: 50 The particle size is 1μm.

[0078] The high temperature humidity sensor resistant to water vapor aging prepared in Comparative Example 1 is recorded as Sensor-D.

[0079] Comparative Example 2 provides a preparation process for a high-temperature humidity sensor resistant to water vapor aging. 50 The particle size is 2μm.

[0080] The high temperature humidity sensor resistant to water vapor aging prepared in Comparative Example 2 is recorded as Sensor-D.

[0081] The high temperature humidity sensors resistant to water vapor aging prepared in Example 1 and Comparative Examples 1-2 were placed in an environment with a temperature of 200°C and a humidity of 95% for testing. The effect of the detection signal change of the high temperature humidity sensors prepared in Example 1 and Comparative Examples 1-2 is shown in detail. Figure 3 .

[0082] Depend on Figure 3 It can be seen that the particle size D of Y2O3-doped stabilized zirconia in Example 1 is 50 The particle size D of Y2O3-doped stabilized zirconia is lower than that of Comparative Example 1-2. 50 , the particle size D of Y2O3-doped stabilized zirconia in Example 1 50 Small, can reduce the precipitation of Y(OH)3, improve the high temperature humidity sensor's resistance to water vapor aging.

[0083] Comparative Example 3 provides an existing zirconia limiting current oxygen sensor purchased from Zhejiang Langde Electronic Technology Co., Ltd., model RSL4.8, recorded as sensor-1.

[0084] Comparative Example 4 provides an existing zirconia limiting current oxygen sensor, Zhejiang Langde Electronic Technology Co., Ltd., model RSL4.8L, recorded as sensor-2.

[0085] The high temperature humidity sensor resistant to water vapor aging prepared in Example 1 and the existing zirconium oxide limiting current oxygen sensor provided in Comparative Examples 3-4 were placed in an environment with a temperature of 200°C and a humidity of 95% for detection. The specific effects of the sensor detection signal changes in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 4 .

[0086] Depend on Figure 4 It can be seen that the water vapor aging-resistant high-temperature humidity sensor prepared in Example 1 of the present application has better water vapor aging resistance than the existing zirconium oxide limiting current type oxygen sensor.

[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A preparation process of a high temperature humidity sensor resistant to water vapor aging, characterized in that: The steps include: Rolling slurry: YSZ powder, dispersant, solvent, binder, and plasticizer are mixed, and zirconium ball mill is added to roll and slurry to obtain slurry. The particle size of the YSZ powder is D 50 0.2-0.5μm; Casting the slurry into a green porcelain tape; Punching holes in the green porcelain belt to form an annular diffusion cavity hole; Printing: Use screen to print cavity slurry in the diffusion cavity hole, the amount of cavity slurry added is 25-30 mg / hole, and use screen to print Pt slurry on the green porcelain tape; Lamination; Cutting; Sintering, the sintering comprising sintering to form a sintered body, chamfering the sintered body and re-firing; The cavity-forming slurry is prepared by mixing amorphous carbon powder and Y2O3 in a mass ratio of (94.5-99.5): (0.5-5.5); the particle size D of Y2O3 in the cavity-forming slurry is 50 It is 50-100nm.

2. The preparation process of a high temperature humidity sensor resistant to water vapor aging according to claim 1, characterized in that: The cavity forming slurry is prepared by mixing amorphous carbon powder and Y2O3 in a mass ratio of 97:

3.

3. The preparation process of a high temperature humidity sensor resistant to water vapor aging according to claim 1, characterized in that: The particle size of Y2O3 in the cavity forming slurry is 80nm.

4. The preparation process of a high temperature humidity sensor resistant to water vapor aging according to claim 1, characterized in that: The particle size D of the YSZ powder 50 It is 0.3μm.

5. The preparation process of a high temperature humidity sensor resistant to water vapor aging according to claim 1, characterized in that: The YSZ powder is 4-6 mol% yttria-stabilized zirconia powder.

6. The preparation process of a high temperature humidity sensor resistant to water vapor aging according to claim 1, characterized in that: The mass ratio of the YSZ powder, dispersant, solvent, binder and plasticizer is 1: (0.01-0.03): (0.5-0.6): (0.17-0.20): (0.06-0.08).

7. The preparation process of a high temperature humidity sensor resistant to water vapor aging according to claim 1, characterized in that: The re-firing temperature is 900-1200° C. and the re-firing time is 1-2 hours.

Citation Information

Patent Citations

  • Preparation method of zirconia-based high-temperature humidity sensor material

    CN113929456A

  • Water-resistant moisture-sensitive device

    JP1990209702A